Serum vitamin D levels and severe therapy resistant asthma in children. (4th April 2011) - Gupta, A; Bush, A; Richards, D; Hawrylowicz, C; Saglani, S
Abstract : Background: Little is known about vitamin D levels and their impact on disease control in children with severe, therapy resistant asthma (STRA). We hypothesised that children with STRA have lower serum vitamin D levels than non-asthmatic controls and that lower vitamin D levels are associated with more severe asthma, (Symptoms, spirometry and inhaled corticosteroid (ICS) treatment; and worse airway inflammation measured in bronchoalveolar lavage (BAL)). Aims: To compare serum vitamin D levels in children with STRA and age-matched non-asthmatic controls, and to investigate the relationship between vitamin D levels and markers of asthma severity, including clinical and therapeutic disease variables. Methods: We measured serum 25-hydroxyvitamin D in 30 asthmatics and 16 non-asthmatic children; asthma severity was categorised using the asthma control test (ACT); spirometry; ICS dose; exhaled nitric oxide at 50 ml/s (FeNO50) as a measure of inflammation; and BAL cytokines. Results: In asthmatics, the prevalence of vitamin D insufficiency (<75 nmol/l) was 90%, with 78% being vitamin D deficient (<50 nmol/l). All age-matched non-asthmatic controls were vitamin D insufficient with 50% being vitamin D deficient. Children with asthma had lower median 25-hydroxyvitamin D serum levels (36 nmol/l, range 3–83) as compared to age-matched non-asthmatic controls (48 nmol/l, range 25–72) (p=0.03). There was a positive correlation between serum 25-hydroxyvitamin D levels and asthma symptoms (ACT) (r=0.49, p<0.001) and per cent predicted forced expired volume in 1 s (FEV1) (r=0.3, p=0.04). Serum 25-hydroxyvitamin D levels were significantly inversely associated with FeNO50 (r=0.6, p=0.001) and ICS usage (r=0.4, p=0.02). In children with STRA, a positive correlation was also noted between serum 25-hydroxyvitamin D levels and BAL levels of the anti-inflammatory cytokine interleukin (IL)-10 (r=0.51, p=0.03). No significant relationship between serum 25-hydroxyvitamin D levels and BAL neutrophils and eosinophils. Conclusion: In children with STRA reduced vitamin D levels are associated with more symptoms lower lung function, more inflammation and greater ICS usage. There is a need for an intervention study, supplementing vitamin D in Vitamin D deficient children who have severe asthma.